Editorial Vol.7(2) - Ahmed, Tahera Ahmed (Bangladesh Journal of Bioethics, 2016)
Hello readers! Hope everyone is fine especially in this season where we often are prone to attacks of cold or flu. The holiday season is at our threshold, and we wish everyone to be in the best of health and happiness. This issue of the BJB is very interesting with topics stretching from Non Communicable Diseases to the ethical issues related to the habitation of the planet Mars, and proves how forward looking are our readers and authors. Mohammad Rashedul Islam et al discuss the application of the SARA method in a district in Bangladesh. The method is based on the principle of Service Availability and Readiness Assessment of WHO. The study in a district in Bangladesh found that about 62% of all the facilities were ready to provide general services like basic amenities with basic equipment, standard precautions for infection prevention, diagnostic capacity and essential medicines. However in case of Non-Communicable Diseases (NCD), only 40% of the health facilities had chronic respiratory disease and cardiovascular diseases diagnosis/management and only 32% had availability of diabetes diagnosis/management. Therefore, service availability and readiness of the health facilities to provide NCD related health services were not satisfactory. The authors emphasize that SARA which is a tool to monitor facilities to be ready for provision of services including NCD, should be used by all clinic managers. The very scientific and forward looking article titled SCNT Method and the Application for Patent Eligibility on Cloned Animals by Norman K. Swazo reviews US federal court decisions regarding applications for patent in the case of live-born animal clones. A decision issued from the United States Court of Appeals for the Federal Circuit established an earlier decision of the Patent Trial and Appeal Board that live-born animals cloned by the somatic cell nuclear transfer method (SCNT) like cattle, sheep, pigs, and goats are not patentable, so a scientist using the method is not eligible for a patent claim on the animals. The author feels that this decision has ethical implications related to the moral status of cloned animals. The author argues whether the end product of a SCNT (somatic cell nuclear transfer) application is same as an invention or only a revelation of nature at the cellular level. The author quotes Article 11 of Universal Declaration on the Human Genome and Human Rights UNDHGR Practices which are contrary to human dignity, such as reproductive cloning of human beings, shall not be permitted. He concludes that the judicial assessments in the USA deciding on the question of patenting of animal clones provide important barriers to human reproductive cloning research, safeguarding moral and legal commitment to human dignity. The article on Ethics in Public Health Research and Clinical Research by Muhammad Waseem Khanet al discusses on the need to continue to focus on ethical values in conducting any research. Tha authors stress the importance, either in public health research or clinical research, of the need to recognize an ethical standard that respects individuals autonomy and communitys wellbeing. This can be achieved through collective collaboration for the protection of individuals autonomy, dignity and wellbeing. Research ethics is a fundamental criterion to be complied with throughout a research study. The very interesting article on Planetary Protection for Mars: Time for Reconsideration by Svetoslav Alexandrov looks into the ethical questions beyond mother earth but which could be affected by people from our planet. In this manuscript the author discusses the ethics of the protection of hypothetical organisms on Mars in terms of planned manned space missions and subsequent colonization. The author discusses the possible problems related to a process called terraformation where the planet is converted to make it suitable for Earth life. He argues that terraformation will change the whole condition of the planet. The author quotes Carl Sagan, of The Planetary Society: If there is life, then I believe we should do nothing to disturb that life. Mars then, belongs to the Martians, even if they are microbes . I think we all agree with this brilliant recommendation. The article We Still Need to Improve Our Research Writing Ethics by Sheikh Arslan Sehgal looks into the value of maintaining professional integrity of research work. Particularly with issues like plagiarism, ethics, authorship and data fabrication. He argues that the scientific community must obey the scientific ethical norms and rules. He feels that ethical problems must be resolved for the advancement of research in countries including Pakistan. The author recommends teaching students the international, institutional and professional standards regarding research and authorship issue. Thus from the beginning researchers will know the key components of ethics in conducting research and the end product will be research work of quality and acceptability. Dear Readers, we look forward to your articles, commentaries, observations on different issues which touch our lives and will help in broadening our knowledge and understanding of Bioethics.